Desmopressin (DDAVP) improves recruitment of activated platelets to collagen but simultaneously increases platelet endothelial interactions in vitro. (February 2014) - Calmer, Simone; Ferkau, Annika; Larmann, Jan; Johanning, Kai; Czaja, Eliana; Hagl, Christian; Echtermeyer, Frank; Goudeva, Lilia; Heuft, Hans-Gert; Theilmeier, Gregor
<x xml:space="preserve">Abstract</x> Platelet dysfunction can cause clinically relevant bleeding. Treatment with DDAVP is advocated for this condition. DDAVP increases von Willebrand factor (VWF) on endothelial cells (ECs) and in plasma. VWF could facilitate platelet deposition on subendothelial collagen. VWF also facilitates platelet/EC interactions. Therefore DDAVP could precipitate thromboembolic events. We used a flow chamber model to study in vitro and ex vivo if DDAVP alters recruitment of platelets to EC and collagen. Resting or TRAP-activated platelets and EC were treated individually or simultaneously with 0.4 ng/ml DDAVP. Fluorophor-labeled platelets (106/ml) were resuspended in reconstituted blood and superfused across EC and collagen in an in vitro flow chamber model at arterial shear (320 s−1). Adhesion of platelets to the respective surface was recorded fluorescence microscopically and platelet covered area was assessed. TRAP significantly induced adhesiveness of platelets for collagen and EC. DDAVP pretreatment of platelets did not affect adhesiveness of resting or TRAP-activated platelets for collagen or EC. Adhesiveness of resting but not TRAP-activated platelets was induced on DDAVP-treated EC. DDAVP-conditioned EC supernatant contained vWF and significantly increased platelet deposition on collagen. Platelets from patients with clinically suspected platelet dysfunction undergoing aortic valve replacement exhibited decreased platelet deposition on collagen surfaces. In summary, our data confirm that DDAVP can induce release of platelet adhesion promoting factors from EC, which is most likely vWF. DDAVP has no direct effect on platelets. Blood samples from DDAVP-treated patients do not exhibit significantly augmented platelet deposition on collagen ex vivo. This influence of released promoting factors might cause an increase of undesirable interactions of platelets with EC.